Studi Komponen Gas Hidrokarbon Batubara Menggunakan Metode Pirolisis Gas Kromatografi (Jurnal Geomine, 2019)
This recent research was conducted to investigate the characteristics of lignite from organic geochemistry side using pyrolysis method of gas chromatography. This aim of the study is to analyze three important things such as the generated hydrocarbon gases, gas volume, and environmental setting. The gas product is called pyrolisat which generated during processing of pyrolysis that shown as chromatogram graph on computer screen which consist of group of short carbon chain (C1-4), medium carbon chain (C5-14), and long carbon chain (>C15). The research result revealed that short carbon chain has dominant percentage (81,9%) than medium carbon chain (9,5%) or long carbon chain (8,6%). This condition indicates that coal sample consisted of various organic matter particularly methane which derived from land plants. Based on these research results, it can be conclude that organic matters were originally from terrestrial environmental setting.